2019
DOI: 10.1097/md.0000000000014596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in myocardial infarction

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 54 publications
3
42
1
3
Order By: Relevance
“…Myocardial infarction (MI) is a cardiovascular disease that has physiological and psychological effects. Feng et al’s study showed that the prevalence of depression among patients with MI was 28.70% (Feng et al 2019 ). Considering the high incidence of COPD, stroke, and MI, all of which lower a patient’s quality of life, there is an urgent need to better understand disease risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial infarction (MI) is a cardiovascular disease that has physiological and psychological effects. Feng et al’s study showed that the prevalence of depression among patients with MI was 28.70% (Feng et al 2019 ). Considering the high incidence of COPD, stroke, and MI, all of which lower a patient’s quality of life, there is an urgent need to better understand disease risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent meta-analysis, 3 the prevalence of depression among MI survivors ranges from 9.17% to 65.88% with a pooled prevalence of 28.70%, making it one of the most common psychiatric comorbidities among MI survivors. A meta-analysis 4 of 29 studies including 16 889 MI survivors observed that there was an increased risk of all-cause mortality, cardiac mortality, and cardiac events with depression among MI survivors.…”
Section: Introductionmentioning
confidence: 99%
“…As doenças cardiovasculares são consideradas a principal causa de morte global, responsáveis por cerca de 17,9 milhões de óbitos no ano de 2016, o que representa em torno de 31% do total de 57 milhões de mortes no mesmo período (Feng et al, 2019;World Health Organization [WHO], 2018). Desse grupo, a doença cardíaca isquêmica foi responsabilizada pela maior parte das mortes em países desenvolvidos e com aumento de incidência em países emergentes (Ahern et al, 2011).…”
Section: Introductionunclassified
“…Outro fator contribuinte e de grande importância no desenvolvimento e na recidiva desse quadro isquêmico, principalmente no período do pós-infarto, é o psicossocial, em que o transtorno depressivo maior está incluído (Larsen, 2013;Lichtman et al, 2014). Feng et al (2019) verificaram, a partir de metanálise envolvendo dez países, que nas últimas décadas houve uma prevalência de casos de depressão em pacientes com diagnóstico prévio de IAM que variou entre 9,17% a 65,88%. Essa variação decorre, sobretudo, das características sociais e demográficas de cada amostra, as quais também influenciam na fisiopatologia do quadro.…”
Section: Introductionunclassified